2015
DOI: 10.1002/ca.22525
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy of the clitoris and its impact on neophalloplasty (metoidioplasty) in female transgenders

Abstract: The current management of female to male transgender surgery is based on the advances in neophalloplasty, perioperative care and the knowledge of the female genital anatomy, as well as the changes that occur to this anatomy with preoperative hormonal changes in transgender population. Since the clitoris plays the main role in female sexual satisfaction, its impact on the outcome in female to male transgender surgery is predictable. Although female genital anatomy was poorly described in majority of anatomical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Stojanovic and Djordjevic () reviewed current knowledge of clitoral anatomy and its relevance to clitoral reconstruction in female‐to‐male sex reassignment surgery. Pauls () reported that the clitoris has an intricate anatomy; therefore, understanding the clitoral frenulum as the anatomical structure stabilizing the clitoris is important, since the clitoris is considered to be central to female orgasmic responses.…”
Section: Discussionmentioning
confidence: 99%
“…Stojanovic and Djordjevic () reviewed current knowledge of clitoral anatomy and its relevance to clitoral reconstruction in female‐to‐male sex reassignment surgery. Pauls () reported that the clitoris has an intricate anatomy; therefore, understanding the clitoral frenulum as the anatomical structure stabilizing the clitoris is important, since the clitoris is considered to be central to female orgasmic responses.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,13,18 Metoidioplasty is advantageous for its capacity to yield “like-with-like” glans reconstruction with tactile and erogenous clitoral tissue, sufficient erectile rigidity without a prosthesis, scarring that is limited to the perineum, and shorter operative times. 5,12,13,20,31 The metoidioplasty-constructed neophallus is often shorter and smaller compared with other techniques; as a result, functional limitations can include difficulty with standing micturition and sexual penetration. 1214,32 Though sometimes touted as a single-stage procedure, a series by Hage and van Turnhout 17 found that, on average, 2.6 procedures were required before a metoidioplasty reconstruction was considered complete.…”
Section: Discussionmentioning
confidence: 99%
“…5,12,13,20,31 The metoidioplasty-constructed neophallus is often shorter and smaller compared with other techniques; as a result, functional limitations can include difficulty with standing micturition and sexual penetration. 1214,32 Though sometimes touted as a single-stage procedure, a series by Hage and van Turnhout 17 found that, on average, 2.6 procedures were required before a metoidioplasty reconstruction was considered complete.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations